Pengaruh Knowledge Sharing, Personal Knowledge, dan Job Prosedure terhadap Kinerja Pegawai di Sekolah Dasar: Studi pada Sekolah Dasar Negeri 1 Tanjungtirto - Afriyanti Eva Belinda Lase; Andia Janash Mumthaza; Niken Widyastuti; Mugi Puspita (Prosiding Seminar Nasional Ilmu Manajemen Kewirausahaan dan Bisnis, 2025)
This study aims to determine the effect of knowledge sharing, personal knowledge, and work procedures on employee performance in Tanjungtirto 1 Public Elementary School. The background of this study is based on the importance of human resource quality in supporting organizational effectiveness, especially in elementary education institutions. The study population was all employees at Tanjungtirto 1 Public Elementary School with data collection using quantitative methods through questionnaires. The data obtained were then analyzed with the help of SPSS software through multiple linear regression tests to test the effect of independent variables on the dependent variable. The results showed that knowledge sharing did not have a significant effect on employee performance, as well as personal knowledge which also did not have a direct effect on performance. In contrast, work procedures were proven to have a positive and significant effect on improving employee performance. In addition, simultaneously knowledge sharing, personal knowledge, and work procedures together had a positive and significant effect on employee performance. This finding means that the existence of clear and structured work procedures has an important role in increasing work effectiveness, while knowledge sharing and personal knowledge require the support of a more focused management system to provide optimal contributions to employee performance in elementary school environments.